ANALISIS PENGARUH PENERIMAAN SISTEM PEMBAYARAN E-CASH TERHADAP INTENSITAS TRANSAKSI NON-TUNAI DI INDONESIA - Afiansyah, Al Razzaq Rofi; Fitri Santi (UNIB Press, 2026)
The development of increasingly sophisticated technology makes it easier for consumers to make transactions. In the past, consumers had to come directly to the store to buy necessities and of course bring some cash, now buying these needs can be easily fulfilled through electronic cash (e-cash) payments. Quantitative research using this online questionnaire will examine the effect of e-cash on non-cash transactions, test the TAM model with perceived ease of use and perceived usefulness variables plus perceived security and risk variables. safety and risk) to non-cash intensity. With 18 questions given to 248 respondents, the population in this study are consumers using e-cash and also consumers who have not used e-cash. From the processed analysis, it shows that perceived usefulness, perceived ease of use and perceived safety and risk have a positive effect on the intensity of non-cash transactions. Practical suggestions in this research for e-cash application service providers are a lot of application development, increasing ease of use and security, as well as increasing features so that the intensity of people who use e-cash applications as a means of payment and transactions in their daily activities is higher.